TINJAUAN KELENGKAPAN REKAM MEDIS RAWAT INAP KASUS BEDAH DI RUMAH SAKIT UMUM MENTENG MITRA AFIA JAKARTA 2021 - Indah Kristina; Nailul Muna Wafiroh (MEDICORDHIF Jurnal Rekam Medis, 2022)
ABSTRACT The purpose of this study was to determine the completeness of the types of forms in the medical records of inpatient surgical cases at the RSU. Menteng Mitra Afia. This study uses a quantitative descriptive method. The total population in this study were all medical records of inpatient surgical cases from January to March 2021 as many as 112 medical records of inpatient surgical cases. The technique of calculating the sample using the slovin formula obtained a total sample of 88 medical records of inpatient surgical cases. The results of the study that, it is known in the RSU. Menteng Mitra Afia does not yet have a Standard Operating Procedure (SPO), from the observations on the medical records of surgical cases, there is no complete medical record. In a review of the types of forms that must have the highest completeness, there are patient identification forms, discharge summaries, and integrated patient progress notes (CPPT) with a percentage of 100%, the highest incompleteness is in the surgical assessment forms, special assessments, and terminal patient assessments with presentations 0%. In the results of the observed consistency for each type of form, the highest completeness was in the author authentication review with an average of 62%, and the lowest completeness was in the good record review with an average of 46%. Factors causing incompleteness are the absence of SPO related to the completeness of inpatient medical records for surgical cases, the absence of a policy regarding the use of types of surgical forms, the absence of socialization of the use of surgical forms and checking only on the operation report form. Keywords: Completeness of Medical Records Inpatient Surgical Cases ABSTRAK Tujuan dari penelitian ini adalah mengetahui kelengkapan jenis-jenis formulir pada rekam medis rawat inap kasus bedah di RSU. Menteng Mitra Afia. Penelitian ini menggunakan metode deskriptif kuantitatif. Jumlah populasi pada penelitiam ini seluruh rekam medis rawat inap kasus bedah pada bulan Januari sampai dengan Maret 2021 sebanyak 112 rekam medis rawat inap kasus bedah. Teknik penghitungan sampel menggunakan rumus slovin didapatkan jumlah sampel sebanyak 88 rekam medis rawat inap kasus bedah. Hasil penelitian bahwa, diketahui di RSU. Menteng Mitra Afia belum memiliki Standar Prosedur Operasional (SPO), dari hasil pengamatan pada rekam medis kasus bedah, tidak ada satu rekam medis yang lengkap. Pada review jenis-jenis formulir yang harus ada kelengkapan tertinggi terdapat pada formulir identitas pasien, ringkasan pulang, dan catatan perkembangan pasien terintegrasi (CPPT) dengan presentase 100%, ketidaklengkapan tertinggi terdapat pada formulir asesmen bedah, asesmen khusus, dan asesmen pasien terminal dengan presentase 0%. Pada hasil kekonsitenan yang diamati pada setiap jenis formulir, kelengkapan tertinggi pada review autentifikasi penulis dengan rata-rata 62%, dan kelengkapan terendah pada review catatan yang baik dengan rata-rata 46%. Faktor penyebab ketidaklengkapan adalah tidak adanya SPO terkait kelengkapan rekam medis rawat inap kasus bedah, tidak adanya kebijakan mengenai penggunaan jenis-jenis formulir bedah, belum adanya sosialisasi penggunaan formulir bedah dan pengecekan hanya dilakukan pada formulir laporan operasi. Kata kunci : Kelengkapan Rekam Medis Rawat Inap Kasus